Evaluation of distribution and management of marine debris on the Pangandaran Coast - Satriawan, Ratu Balqist Priesty Higina; Ihsan, Yudi Nurul; Herawati, Titin; Nurhayati, Atikah; Yuniarti, Yuniarti; Sunarto, Sunarto (Acta Aquatica: Aquatic Sciences Journal, 2024)
The increasing number of tourist visits and activities of coastal communities affects the distribution of marine waste on the Pangandaran coast, resulting in waste generation that pollutes the coastal environment. This is due to a lack of awareness in disposing of waste in its proper place, a lack of cleaning facilities and a waste transport fleet by the Pangandaran district government. The aim of this research is to provide an evaluation regarding the distribution of marine waste and its management on Pantai Timur, Pantai Barat and Pantai Madasari. Using Survey Method and Driving Force-Pressure-State-Impact-Response data analysis. The research location was carried out in three locations, namely on the Pantai Timur, Pantai Barat and Pantai Madasari. The results of this research are that the distribution of marine debris on Pantai Timur, Pantai Barat and Pantai Madasari is categorized as moderate. This causes pressure on coastal areas where there is waste generation at several research stations. The most common type of waste is plastic waste with a percentage of 45-54% on Pantai Timur, 36-55% on Pantai Barat and 43-51% on Pantai Madasari. The type of waste that is least found is rubber with a percentage of 2-3%. The actions taken by Pangandaran Village and the Pangandaran Regency Environment and Hygiene Service (DLHK) are waste management using a collect-transport-dispose system, community service to clean the beach with the community on Fridays, and the availability of several rubbish bins at every distance of 10 meters. Waste management on Pantai Madasari is managed by the village government, where this authority is handed over to Village-Owned Enterprises using a collect-transport-dispose system and burned directly at the temporary disposal site (TPS).Keywords: Coastal; DPSIR; plastic; pollution; waste distribution